2020
DOI: 10.3390/cancers12082183
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cell Acid Adaptation Gene Expression Response Is Correlated to Tumor-Specific Tissue Expression Profiles and Patient Survival

Abstract: The acidic pH of the tumor microenvironment plays a critical role in driving cancer development toward a more aggressive phenotype, but the underlying mechanisms are unclear. To this end, phenotypic and genotypic changes induced by adaptation of cancer cells to chronic acidosis have been studied. However, the generality of acid adaptation patterns across cell models and their correlation to the molecular phenotypes and aggressiveness of human cancers are essentially unknown. Here, we define an acid adaptation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 74 publications
1
25
0
Order By: Relevance
“…These, and many other studies, were biassed by design, in the sense that the hypothesis was testing the pHe sensitivity of an a priori defined target, rather than taking a more agnostic approach towards the identity of the putative H + sensor. To address this concern, recent studies have sought evidence for pHe-sensitive pathways using unsupervised discovery pipelines, such as transcriptomics [75,76], proteomics [76,77], or metabolomics [78,79]. The general conclusion from these studies is that a decrease in pHe triggers a multifaceted response that involves a change in phospholipid composition [79], increases glutaminolysis and fatty acid synthesis [78], induces autophagy [80,81], remodels the extracellular matrix [75,82], modulates the cell cycle [75], affects DNA repair [75], promotes epithelial-mesenchymal transition (EMT) [83], and increases alternative splicing [84].…”
Section: The Case For Studying Acidosis In Cancer Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…These, and many other studies, were biassed by design, in the sense that the hypothesis was testing the pHe sensitivity of an a priori defined target, rather than taking a more agnostic approach towards the identity of the putative H + sensor. To address this concern, recent studies have sought evidence for pHe-sensitive pathways using unsupervised discovery pipelines, such as transcriptomics [75,76], proteomics [76,77], or metabolomics [78,79]. The general conclusion from these studies is that a decrease in pHe triggers a multifaceted response that involves a change in phospholipid composition [79], increases glutaminolysis and fatty acid synthesis [78], induces autophagy [80,81], remodels the extracellular matrix [75,82], modulates the cell cycle [75], affects DNA repair [75], promotes epithelial-mesenchymal transition (EMT) [83], and increases alternative splicing [84].…”
Section: The Case For Studying Acidosis In Cancer Researchmentioning
confidence: 99%
“…To address this concern, recent studies have sought evidence for pHe-sensitive pathways using unsupervised discovery pipelines, such as transcriptomics [75,76], proteomics [76,77], or metabolomics [78,79]. The general conclusion from these studies is that a decrease in pHe triggers a multifaceted response that involves a change in phospholipid composition [79], increases glutaminolysis and fatty acid synthesis [78], induces autophagy [80,81], remodels the extracellular matrix [75,82], modulates the cell cycle [75], affects DNA repair [75], promotes epithelial-mesenchymal transition (EMT) [83], and increases alternative splicing [84]. However, when interpreting these results, it is important to consider the precise level of pHe attained during measurements and how this change was made experimentally.…”
Section: The Case For Studying Acidosis In Cancer Researchmentioning
confidence: 99%
“…Recent studies reported that tumor cells adapt to long-term acidosis. Exposing tumor cells to low pH for 4 weeks or longer induced changes in protein expression and functional properties [ 33 36 ]. In order to analyze whether the changes in gene expression described above are the result of a short-term acidification (24 h) or can also be found in tumor cells chronically adapted to low pH, AT1 cells were kept for 11 passages (5 weeks) at pH 6.6.…”
Section: Resultsmentioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma (PDAC) cell lines AsPC1, MIA-PaCa-2 and PANC1 were a gift from Prof. Anna Trauzold (Christian-Albrecht University, Kiel, Germany), maintained in RPMI (Sigma-Aldrich, R0883) supplemented with 10% FBS, 1% penicillinstreptomycin mixture, 1% GlutaMAX (35050-038, Gibco, Waltham, MA, USA), 1% sodium pyruvate (11360-039, Gibco, Waltham, MA, USA), and used within passage 3-8 [29,30]. Adult mouse myocytes were isolated from Langendorff-perfused mice hearts using a previously published method [31,32].…”
Section: Cellsmentioning
confidence: 99%